Mepolizumab therapy improves the most bothersome symptoms in patients with hypereosinophilic syndrome - Roufosse, Florence; Butterfield, Joseph; Steinfeld, Jonathan; Bentley, Jane H.; von Maltzahn, Robyn; Kwon, Namhee; Nelsen, Linda (Frontiers in Medicine, 2023)
Background: Hypereosinophilic syndrome (HES) is characterized by persistent elevated blood and/or tissue eosinophil levels and eosinophil-mediated organ damage. Presentation is highly heterogenous; patients may experience symptoms affecting multiple organ systems. Objectives: To assess the effects of mepolizumab, which targets interleukin-5, on HES-related symptom burden, based on HES daily symptoms (HES-DS) questionnaire data collected during the Phase III (ClinicalTrials.gov ID: NCT02836496) study of mepolizumab in patients with HES. Methods: Each of the six HES-related symptoms were rated (0–10) daily by patients, recalling worst symptom experience in the prior 24 hours; change from baseline at Week 32 was also calculated for mepolizumab versus placebo. Results: Mepolizumab versus placebo reduced HES-related symptom burden severity in patients with HES at Week 32. Improvements in the median change from baseline scores were seen across all symptom groups except skin for patients treated with mepolizumab; greatest improvement from baseline was observed for breathing symptoms. Conclusion: These data highlight the considerable symptom burden associated with HES and further support the clinical benefits of mepolizumab treatment for these patients. Funding: GSK (200622)